Ternary complementary sets and its application in UWB - WANG Shi-ji; ZHANG Nai-tong (Tongxin xuebao)
Ternary complementary set based UWB signaling employing a set of orthogonal chip pulses was proposed for DS-UWB.It had many advantages in indoor high-speed short range communications.First the system model of multiple access communications was founded,then ternary complementary set and its recursive construction method were analyzed,and then the performance evaluation structure of multiple access communications based the ternary complementary sets by use of the Rake receiver was put forward.Ternary complementary sets assigned to two users had good aperiodic autocorrelation functions.Hence,the multipath interference as well as multiple access interference were mitigated.Simulation results show that ternary MO complementary sets have better performances compared with other random sequences in the SV/IEEE 802.15.3a channel model.